Knowledge based refinement - Anh, Dao Nam (Journal of Computer Science and Cybernetics, 2016)
In the work knowledge based refinement in close relation with inference is considered. It proposes a new approach based on the notion of conflicts. A mathematical formulation for resolving conceptual conflicts among rules is developed. The conceptual conflicts are begot in probabilistic reasoning and then they are eliminated in machine learning. Knowledge based refinement is processed as learning from the conflicts’ discovery.